Multimodal intervention in 8- to 13-year-old French dyslexic readers: Study protocol for a randomized multicenter controlled crossover trial - Karine Louna Harrar-Eskinazi; Bruno De Cara; Gilles Leloup; Julie Nothelier; Hervé Caci; Johannes C. Ziegler; Sylvane Faure (BMC, 2022)
Abstract Background Developmental dyslexia, a specific and long-lasting learning disorder that prevents children from becoming efficient and fluent readers, has a severe impact on academic learning and behavior and may compromise professional and social development. Most remediation studies are based on the explicit or implicit assumption that dyslexia results from a single cause related to either impaired phonological or visual-attentional processing or impaired cross-modal integration. Yet, recent studies show that dyslexia is multifactorial and that many dyslexics have underlying deficits in several domains. The originality of the current study is to test a remediation approach that trains skills in all three domains using different training methods that are tailored to an individual's cognitive profile as part of a longitudinal intervention study. Methods This multicenter randomized crossover study will be conducted in three phases and will involve 120 dyslexic children between the ages of 8 and 13 years. The first phase serves as within-subject baseline period that lasts for 2 months. In this phase, all children undergo weekly speech-language therapy sessions without additional training at home (business-as-usual). During the second phase, all dyslexics receive three types of intensive interventions that last 2 month each: Phonological, visual-attentional, and cross-modal. The order of the first two interventions (phonological and visual-attentional) is swapped in two randomly assigned groups of 60 dyslexics each. This allows one to test the efficacy and additivity of each intervention (against baseline) and find out whether the order of delivery matters. During the third phase, the follow-up period, the intensive interventions are stopped, and all dyslexics will be tested after 2 months. Implementation fidelity will be assessed from the user data of the computerized intervention program and an "intention-to-treat" analysis will be performed on the children who quit the trial before the end. Discussion The main objective of this study is to assess whether the three types of intensive intervention (phase 2) improve reading skills compared to baseline (i.e., non-intensive intervention, phase 1). The secondary objectives are to evaluate the effectiveness of each intervention and to test the effects of order of delivery on reading intervention outcomes. Reading comprehension, spelling performance and reading disorder impact of dyslexic readers are assessed immediately before and after the multimodal intervention and 2 months post-intervention. Trial registration ClinicalTrials.gov , NCT04028310. Registered on July 18, 2019.